2021
DOI: 10.3390/polym13040585
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Zinc Waste Filler on the Tribological and Mechanical Properties of Silicone-Based Composites

Abstract: Silicones are often used for various types of coatings, but due to their poor mechanical properties, they often require modification to meet specific requirements. At the same time, various production processes throughout the world generate different types of waste, the disposal of which is harmful to the environment. One possible solution is to use production waste as a filler. In this paper, the authors investigated how the use of metallurgical production waste products as fillers changed the mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The introduction of these two fillers at concentrations of 2.5, 5, 7.5, and 10 wt% was carried out to reduce the abrasion of the obtained composite materials, in relation to the native silicone, when used as the matrix. In relation to the results presented in the previous publication [ 28 ], the authors found similar trends after introducing both zinc and manganese compounds into the silicone. In the case of the abrasive wear test, carried out on the Schopper-Schlobach apparatus, a decrease in the abrasive wear was noticed for all of the composites, when compared to the sample made of silicone F128.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The introduction of these two fillers at concentrations of 2.5, 5, 7.5, and 10 wt% was carried out to reduce the abrasion of the obtained composite materials, in relation to the native silicone, when used as the matrix. In relation to the results presented in the previous publication [ 28 ], the authors found similar trends after introducing both zinc and manganese compounds into the silicone. In the case of the abrasive wear test, carried out on the Schopper-Schlobach apparatus, a decrease in the abrasive wear was noticed for all of the composites, when compared to the sample made of silicone F128.…”
Section: Discussionsupporting
confidence: 84%
“…This study is a continuation of previous research [ 28 ] in which authors investigated the introduction of zinc waste as a filler in silicon-based composites and its effect on the mechanical and tribological properties of the material. The obtained results showed that for 5 to 20% filling, the addition of both the zinc dust, and the sifted and non-sifted zinc ash improved the tribological properties and reduced the abrasive wear of the material.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Currently, a main focus of the manufacturing industry is determining the possibility of composite material applications, which often replaces those in previous use [ 7 , 8 ]. Polymer materials can become the matrix of the composite, which, depending on the type of filler, can change the physicochemical or biological properties that are most desirable in a given situation [ 9 , 10 ]. Choosing the right filler can increase mechanical strength and reduce abrasion at the same time [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%